A comprehensive data analysis of e-bike mobility and greenhouse gas emissions in a higher education community: IPBike study of case - Beatriz Flamia Azevedo; Kelson Metzger; Ana I. Pereira (SN Applied Sciences, 2023)
Abstract Sustainable mobility is a goal for several countries. This kind of mobility depends not only on personal motivation but also on government actions. Encouraging people, particularly children and younger, to raise awareness of the importance and benefits of using sustainable transport, like bicycles, is crucial to developing a sustainable society. This work presents the IPBike project, a Portuguese project applied at the Polytechnic Institute of Bragança. This project aims to promote the use of sustainable transport in the academic community through a rental bike program. This paper presents the results of the over three years of the IPBike project, as well as the user’s impressions and suggestions to improve the project. Moreover, a greenhouse gas emission reduction is estimated, comparing the displacement using bikes or only by cars. In general, the results achieved are promising to promote sustainable cities and plan the future since the bikes of the project are constantly rented and the user’s positive feedback, which makes the IPBikes a popular community asset. Moreover, the results demonstrate a bike-sharing program’s capacity to impact people’s lives, improve their health, reduce travel expenses, and impact society and the environment. Besides, according to the estimates, the IPBikes provided a reduction of 7% per year in the greenhouse gases emitted by the users, which means a significant reduction all over the project implantation.